2021
DOI: 10.3892/mco.2021.2361
|View full text |Cite
|
Sign up to set email alerts
|

Fascin‑1 is associated with recurrence in solitary fibrous tumor/hemangiopericytoma

Abstract: Fascin-1, an actin-bundling protein, is associated with poor prognosis in patients with various types of human carcinoma. However, research is limited on the role of fascin-1 in sarcoma. Solitary fibrous tumor (SFT) and hemangiopericytoma (HPC) are rare sarcomas derived from the mesenchyme. Although the prognosis of SFT/HPC is generally favorable, fatalities are possible with repeated recurrence and distant metastasis. The current study included a total of 20 Japanese patients, who were diagnosed with SFT/HPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Fascin also exists in different tissues of the human body, such as mesenchyme and nervous tissue, however, it is not present in most normal epithelia. Its correlation to malignancy has also been reported in various carcinomas and sarcomas [ 23 , 24 , 25 , 26 , 27 ]. Although, unlike Nestin, there is no commonly accepted role of Fascin regarding melanoma malignancy [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Fascin also exists in different tissues of the human body, such as mesenchyme and nervous tissue, however, it is not present in most normal epithelia. Its correlation to malignancy has also been reported in various carcinomas and sarcomas [ 23 , 24 , 25 , 26 , 27 ]. Although, unlike Nestin, there is no commonly accepted role of Fascin regarding melanoma malignancy [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 89%
“…Nestin expression is observed in various embryonic cells and tissues, and a correlation of Nestin expression to clinical malignancy has been reported in melanoma and other tumors, such as breast cancer, ovarian cancer, and osteosarcoma [ 13 , 14 , 18 , 21 , 22 ]. Fascin, an actin-bundling protein, plays an important role in the regulation of cell adhesion, migration and invasion [ 23 , 24 , 25 , 26 , 27 ]. Fascin also exists in different tissues of the human body, such as mesenchyme and nervous tissue, however, it is not present in most normal epithelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Immunostaining of Fascin-1, a protein involved in cell migration and invasion, has also shown great potential in predicting patient prognosis. In a study performed by Yamamoto et al, 11 Fascin-1 has a strong association with tumor recurrence ( P < .05). Metastasis of SFT/HPC can occur several years after the initial diagnosis, even after total gross resection of the tumor, with a mean time of 7.5 years.…”
Section: Discussionmentioning
confidence: 90%
“…These results showed that SFTs occurring in the oral region have a low risk of recurrence. However, it has been reported that recurrence is more likely to occur when the Ki-67 positivity rate in SFT tumor cells exceeds 5% 8 . In our case, although no evidence of necrosis was observed in the tumor cells, the Ki-67 positivity rate was 5%, suggesting that careful follow-up was necessary.…”
Section: Discussionmentioning
confidence: 99%